PERSEPSI MASYARAKAT TENTANG PENDIDIKAN LUAR SEKOLAH STUDI FENOMENOLOGI PADA MASYARAKAT DESA OEMATNUNU DUSUN 03 RT 005 RW 006 KECAMATAN KUPANG BARAT - Kosapilawan, Regina Sarci; Mardani, Ambara Saraswati; Makleat, Nirwaning (Universitas Nusa Cendana, 2023)
ABSTRACT The problem raised in this study is how is the public's perception of Non Formal Education in Oematnunu Village, Dusun 03 RT 005 RW 006, West Kupang District. The purpose of this study was to determine the public's perception of Non-Formal Education in Oematnunu Village, Dusun 03 RT 005 RW 006, West Kupang District. The type of research used is qualitative research using a phenomonology strategy used to interpret the experience of an informant in giving his perceptions about Non Formal Education. Data collection techniques using observation techniques, documentation, and interviews. In this study, the research informants were the people of Oematnunu Village who had participated in Non-Formal Education programs. Based on the results of the study it can be concluded that the public's perception of Non Formal Education is quite good. The community's perception above shows that the majority say Non-Formal Education is a package school where schools are for people who are illiterate and drop out of education. There are also those who say that extracurricular education is special education, extracurricular activities, etc. The community can give their perceptions about Outdoor Education because there are influencing factors such as experience, needs and external stimuli.